A remarkable case of pleural effusion - Castelbranco-Silva, Ana (2022)
Tuberculosis is rare in pediatric age but remains an issue in populations with risk factors. A new pediatric diagnosis frequently reflects a recent infection in the community. Herein is reported the case of an adolescent with prolonged but well-tolerated dyspnea, anorexia, fever, and night sweats, whose radiograph showed a massive pleural effusion. Pleural fluid analysis was compatible with pleural TB, and pleural biopsy confirmed the diagnosis. Pleural fluid polymerase chain reaction was later positive for Mycobacterium tuberculosis, and interferon-gamma release assay was also positive.